MANAJEMEN PENGEMBANGAN TENAGA PENDIDIK DALAM MENINGKATKAN MUTU PEMBELAJARAN DI MADRASAH IBTIDAIYAH AL-FALAH PESANGGRAHAN - Halimatus Sa’diyah (Nusantara Journal of Islamic Studies, 2023)
This study aims to determine the principal, student discipline, and the role of the principal's leadership in improving student discipline at MA AL-FALAH Jangkar. This study uses a qualitative approach with a descriptive research type. In collecting data, researchers used observation, interview, and documentation methods to obtain in-depth and comprehensive information about the role of the principal's leadership at MA Al-Falah and student discipline at MA Al-Falah. The results of the study showed that the role of the principal greatly influenced student learning achievement, especially student discipline. Based on the results of this study, it shows that the increase in student discipline at MA Al-Falah Jangkar is quite good, but there are still shortcomings in enforcing regulations.